1990
DOI: 10.1080/00420989020080321
|View full text |Cite
|
Sign up to set email alerts
|

The Wage Effects of Residential Location and Commuting Constraints on Employed Married Women

Abstract: It has been argued that greater spatial constraints are imposed on the job searches of women workers and that these greater constraints account for some of the gender wage gap. All researchers agree that women commute shorter distances to work than men. In addition, some researchers have argued from indirect evidence that two-earner households give greater weight to husbands' job opportunities when choosing a residential location. In this paper, we use data on two-earner households from the 1980 Public Use Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 8 publications
1
35
0
Order By: Relevance
“…In summary, most of the above studies find some support for the spatial mismatch hypothesis for black and Hispanic women. The evidence is tentative, however, and limited either to highly aggregate studies across metropolitan areas or, as in Madden and Chui (1990) and McLafferty and Preston (1991), to narrowly defined categories of workers. Moreover, studies have not adequately investigated whether commuting differences reflect differences in earnings and access to transportation or an explicitly spatial mismatch between jobs and residences.…”
Section: Gender Labor Market Segmentation and Spatial Mismatchmentioning
confidence: 93%
“…In summary, most of the above studies find some support for the spatial mismatch hypothesis for black and Hispanic women. The evidence is tentative, however, and limited either to highly aggregate studies across metropolitan areas or, as in Madden and Chui (1990) and McLafferty and Preston (1991), to narrowly defined categories of workers. Moreover, studies have not adequately investigated whether commuting differences reflect differences in earnings and access to transportation or an explicitly spatial mismatch between jobs and residences.…”
Section: Gender Labor Market Segmentation and Spatial Mismatchmentioning
confidence: 93%
“…For example, Hesley and Strange [13] illustrate how agglomeration itself can be driven by increasing expected urban match quality, while Wheeler [34] shows how decreasing search costs lead to more productive matches, increased sorting and wages in urban labor markets. Evidence suggests that women are less spatially mobile than men, with job search conducted over a smaller area than men (Madden and Chiu [19]). Hence, denser markets and better job matching may counterbalance this reduced mobility.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of reasons why such gender differences might exist. First, empirical evidence suggests that women are less spatially mobile than men, with job search conducted over a smaller area than men (Madden and Chiu [19]). In denser urban labor markets, improved urban job matching may counterbalance this reduced mobility and hence, one might expect that any urban wage premium would be larger for women than men.…”
Section: Introductionmentioning
confidence: 99%
“…Not only do more women find work from a fixed home address, but a series of studies including Hecht (1974), Madden (1981), Fagnani (1983), Hanson and Johnston (1985), Pratt (1988a, 1988b), and McLafferty (1990, 1991) have found that women travel shorter distances to work, although in the last case, travel time differences in Toronto were insignificant. In a study of office journeys-towork in five U.K. towns (Watford, Reading, Southampton, Swindon, and Liverpool), Daniels (1980) found consistently shorter travel distances for women; time differences showed a similar pattern but were much less marked.…”
Section: Home and Work And Locality A Conceptualizationmentioning
confidence: 95%